The Economics of Infectious Diseases - Auld, M. Christopher; Fenichel, Eli P.; Toxvaerd, Flavio (Journal of Economic Literature, 2025)
We synthesize the literature on economic epidemiology, the interdisciplinary field that draws on the ideas and methods of economics to analyze individual behavior, aggregate disease dynamics, and public policy during infectious disease epidemics. We cover the main models of individual behavior during epidemics, related econometric evidence, and models of disease dynamics appropriate for the analysis of a range of infectious diseases. We outline modeling approaches to a range of control measures including non-pharmaceutical interventions such as stay-at-home mandates, quarantines, and sheltering, and pharmaceutical interventions such as vaccines and treatment. Last, we characterize different types of externalities and heterogeneities and discuss the targeting and implementation of policies through restrictions and incentives. (JEL D62, D91, H51, I12, I18)